ZAKAZ REKLAMY A PRAWO DO RZETELNEJ INFORMACJI (W ŚWIETLE PRZEPISÓW O ADWOKATURZE) - Masiota, Aleksandra; Masiota, Jacek (Wydział Prawa i Administracji UAM, 2002)
The interdiction to advertise attorneys’ services, although sometimes claimed to violate the freedom of speech, is a limitation consciously self-imposed by the corporation, as it has been considered deontologically sound according to the Bar Code of Conduct. Yet, although ethical norms prevent attorneys from advertising themselves, they are allowed to provide information concerning their services. This freedom, secured in art.61 o f the Code in relation with art. 8 point 2 o f the Polish Constitution, gives the right for reliable and complete information concerning the activity of organs which perform their duties imposed by force of freelance profession self-government. Additionally, it is worth considering the future of freelance profession codes of conduct, including the Bar code. Leaving them unchanged might result in their trivialisation, i.e. they might turn from deontic codes into codes o f wishful thinking and accounts of desirable manners of conduct set out to corporation members as a goal to be attained. When it comes to professional ethics, this is the case in the USA, where the law imposes no obligations even in ethically unambiguous situations.
INTERDICTION TO ADVERTISE ATTORNEYS’ SERVICES AND THE RIGHT FOR RELIABLE AND COMPLETE INFORMATION (IN THE LIGHT OF REGULATIONS ON THE BAR)